Analysis of basic soccer techniques for Junior High School extracurricular players - Riko Riko; Syafaruddin Syafaruddin; Herri Yusfi (Universitas Sriwijaya, 2024)
Basic technical ability is an important element for soccer players. However, analysis of these skills for beginners are very rarely done. Even though with the analysis, the coach can help to optimize the game of the novice team. The research conducted is a quantitative descriptive study that aims to determine how much ability each extracurricular soccer player has. This research was conducted in November-December 2023 at SMPN 3 Pangkalpinang. The population of this study were extracurricular soccer players of SMPN 3 Pangkalpinang with a sample of 30 people. Based on the test results, it is known that the passing and control abilities of the sample have an average calculation obtained of 14.73 points which are included in the moderate category, the average test results of basic technical abilities in the dribbling test results obtained 19.95 seconds which are also included in the moderate category, and the results of the level of shooting ability of extracurricular soccer students of SMP Negeri 3 Pangkalpinang are included in the moderate category with an average of 8.9 points.